2019
DOI: 10.1111/lang.12346
|View full text |Cite
|
Sign up to set email alerts
|

Gestures and Words in Naming: Evidence From Crosslinguistic and Crosscultural Comparison

Abstract: We report on an analysis of spontaneous gesture production in 2-year-old children who come from three countries (Italy, United Kingdom, Australia) and who speak two languages (Italian, English), in an attempt to tease apart the influence of language and culture when comparing children from different cultural and linguistic environments. Eighty-seven monolingual children aged 24-30 months completed an experimental task measuring their comprehension and production of nouns and predicates. The Italian children sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
(99 reference statements)
1
8
0
1
Order By: Relevance
“…T. Hall, 1976), and as such one might argue that our results might not generalize to low gestural languages. However, while Cattani et al (2019) found Italian children outperform English children in the production of representative and pointing gestures (but curiously not Australian children), Liszkowski et al (2012) found no differences in the production of pointing gestures across seven different languages. Clearly further work is needed to establish specifically whether means of deictic communication differ across languages.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…T. Hall, 1976), and as such one might argue that our results might not generalize to low gestural languages. However, while Cattani et al (2019) found Italian children outperform English children in the production of representative and pointing gestures (but curiously not Australian children), Liszkowski et al (2012) found no differences in the production of pointing gestures across seven different languages. Clearly further work is needed to establish specifically whether means of deictic communication differ across languages.…”
Section: Discussionmentioning
confidence: 89%
“…First, there is somewhat mixed evidence that languages differ in the extent to which gestures are utilized. Italian has been regarded as a high gestural language (Kendon, 2004) with a ‘high-context’ communication style (Cattani et al, 2019; E. T. Hall, 1976), and as such one might argue that our results might not generalize to low gestural languages.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, there are many previous works on the adaptation of parental input to the communicative development of the child that have focused on infants of approximately 16 months. As suggested by Cattani et al (2019), ‘At around 16 months, children become easily able to map both words and gestures to objects, actions, or events, resulting in a substantial equipotentiality between the verbal and gestural modalities (Abrahamsen, 2013; Volterra et al, 2005)’ (p. 711). Thus, analyzing the interactions of parents with their 16 months old infants can allow us to detect the similarities and differences between mothers and fathers in their bimodal communication with their infants.…”
Section: Parental Communicative Input Across Different Contexts: Dyad...mentioning
confidence: 99%
“…Es necesario, en este sentido, que más estudios de otras culturas y utilizando metodologías cuantitativas sean efectuados, de modo de poder replicar los resultados hallados y corroborar o rechazar los datos de los cuales se dispone. En este sentido, en otros estudios transculturales se encontró que, además del nivel socioeconómico, la forma en la que los adultos regulan la comunicación de sus infantes, las prácticas de crianza y las formas de interacción (diádicas y grupales), inciden en la adquisición y producción de la comunicación verbal y no verbal (Cattani et al, 2019;Hoff & Tian, 2005). Es necesario agregar que más estudios en castellano deberían ser realizados para ampliar el acceso al conocimiento sobre la temática.…”
Section: Masculino = 83 Femenino= 75unclassified